2022
DOI: 10.21203/rs.3.rs-1413730/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The m assive d ifferences in d iet i nduced an a ltered g ut m icrobiota s tructure in m andarin d uck  ( Aix g alericulata )  at b reeding a rea

Abstract: Animal gut is a dynamic ecosystem, and there are many factors affecting the structure of intestinal flora and the diversity of intestinal microbes, among which food differences are the direct causes. To investigate the effect of food composition on the intestinal flora structure of mandarin duck during the reproductive period, 9 feces were collected from 2 foraging sites of Shiqian Mandarin Duck Lake National Wetland Park, Guizhou, China. We analyzed the chloroplast rbcL gene, mitochondrial COI gene and 16S rR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Expect for the AIE property of the sugar-based materials mentioned above, the researchers also have discovered that some kinds of saccharides, such as starch, cellulose, and their 5), glucose (6), lyxose (7), mannose (8), methyl a-glucopyranoside (9), rhamnose (10), ribose (11), sorbose (12), xylose (13), cellobiose (14), lactose (15), maltose (16), maltulose (17), melibiose (18), sucrose (19), trehalose (20), melezitose (21), raffinose (22), acarbose (23), arabinose (24), 2-deoxy-lyxohexos (25), tagatose (26), gentiobiose (27), lactulose (28), palatinose (29), turanose (30), maltotriose (31), and maltopentose (32) derivatives, could present novel room temperature phosphorescence (RTP) properties. 212−214 As shown in Figure 76, Yuan, Zhang, and Tang et al found that some natural sugars such as starch and cellulose powders could emit RTP at 470 and 427 nm with lifetime as 4.98 and 4.66 μs, respectively.…”
Section: Aie Mechanism Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Expect for the AIE property of the sugar-based materials mentioned above, the researchers also have discovered that some kinds of saccharides, such as starch, cellulose, and their 5), glucose (6), lyxose (7), mannose (8), methyl a-glucopyranoside (9), rhamnose (10), ribose (11), sorbose (12), xylose (13), cellobiose (14), lactose (15), maltose (16), maltulose (17), melibiose (18), sucrose (19), trehalose (20), melezitose (21), raffinose (22), acarbose (23), arabinose (24), 2-deoxy-lyxohexos (25), tagatose (26), gentiobiose (27), lactulose (28), palatinose (29), turanose (30), maltotriose (31), and maltopentose (32) derivatives, could present novel room temperature phosphorescence (RTP) properties. 212−214 As shown in Figure 76, Yuan, Zhang, and Tang et al found that some natural sugars such as starch and cellulose powders could emit RTP at 470 and 427 nm with lifetime as 4.98 and 4.66 μs, respectively.…”
Section: Aie Mechanism Studymentioning
confidence: 99%
“…(F) Fluorescent-R channel images (exposure time 30 ms). Saccharides: allose (1), 2-deoxyribose (2), fructose (3), fucose (4), galactose (5), glucose(6), lyxose(7), mannose(8), methyl a-glucopyranoside (9), rhamnose(10), ribose(11), sorbose(12), xylose(13), cellobiose(14), lactose(15), maltose(16), maltulose(17), melibiose(18), sucrose(19), trehalose(20), melezitose(21), raffinose(22), acarbose(23), arabinose(24), 2-deoxy-lyxohexos(25), tagatose(26), gentiobiose(27), lactulose(28), palatinose(29), turanose(30), maltotriose(31), and maltopentose(32). Adapted from ref 211.…”
mentioning
confidence: 99%
“…14 It has many pharmacological activities of blood coagulation function, tumor suppressor, vasodilation, and nerve nutrition. 15 16 17 In addition, Wu et al 18 found that through the phosphoinositide-3 kinase/protein kinase B (PI3K/AKT) signaling pathway, transcinnamaldehyde in Guizhi (Ramulus Cinnamomi) can inhibit the level of interleukin-1β (IL-1β) and the inflammatory response of chondrocytes and prevent joint damage, suggesting that some active ingredients in Guizhi (Ramulus Cinnamomi) are beneficial to the treatment of bone and joints and it needs further research.…”
Section: Huangqi Guizhi Wuwu Decoctionmentioning
confidence: 99%
“…7 The large surface area-to-volume ratio of the electrospun membrane is a favorable attribute for drug delivery applications, 8 tissue repair, biological dressing, enzyme immobilization, etc. 8,9 The versatility of the technique lies in the fact that different processing modifications are possible with it including multiple fluid processing like co-axial electrospinning, 10 side-by-side electrospinning, 11 tri-axial electrospinning, 12,13 etc. Recently, fabrication of fibrous membranes with "smart" properties is gaining much attention also.…”
Section: Introductionmentioning
confidence: 99%